Mobilising marine biodiversity data: a new malacological dataset of Italian records (Mollusca) - Arianna Giannini; Massimo Appolloni; Luigi Romani; Marco Oliverio (Biodiversity Data Journal)
The location and palaeoceanographic history of the Mediterranean Sea make it a biodiversity hotspot, prompting extensive studies in this region. However, despite the marine biodiversity of this area being apparently widely studied, a large amount of distributional data for Mediterranean taxa is still unpublished or scattered in various sources and formats, causing severe limitations to their potential reuse. This emerges as a particularly thorny issue for highly biodiverse and neglected taxa, such as invertebrates. The mobilisation of these frozen data through a process of standardisation and georeferencing could potentially support biodiversity research and conservation. The aim of this work is to provide a standardised pipeline to integrate these dispersed data, focusing on the Italian waters of the Mediterranean Sea and using molluscs as target taxa. Data were gathered from two main sources: published literature and Natural History Collections. The harmonisation process involved three key steps: 1) terminology and structure standardisation; 2) taxonomy updating and 3) georeferencing. Our efforts yielded over 44000 standardised records of mollusc species from Italian seawaters. These records encompassed primary biodiversity data from newly-digitised specimens owned by 11 different institutions and private collectors, as well as secondary biodiversity data extracted from 311 published studies.This work is the first attempt to mobilise the available distributional information of Italian marine mollusc species from Natural History Collections and literature, converting the retrieved data into point-occurrence records through standard protocols, thus creating a FAIR (Findable, Accessible, Interoperable and Reusable) dataset collating these records from Italian marine sectors.